PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS IV SDN 1 KARANGTENGAH - Nurul Khafiyyani; Aiman Faiz; Nurkholis (STKIP Subang, 2023)
The background of this research is the low critical thinking skills of students in Mathematics learning, aiming to improve the critical thinking skills of fourth grade students at SDN 1 Karantengah, Karangsembung District, Cirebon Regency through the Problem Based Learning (PBL) learning model. This research is a classroom action research in which the researcher collaborates with the class IV teacher at SDN 2 Kubangkarang as an observer. The research subjects were 13 students of grade IV SDN 1 Karangtengah, consisting of 7 male students and 6 female students. The techniques used in data collection are tests, observations, interviews, field notes and documentation. The data obtained are in the form of test results as primary data and results of observations, interviews, field notes, and documentation as support. The data analysis technique used is quantitative descriptive analysis to analyze the results of the final test for each action. The research was conducted in two cycles. The results showed that the application of the Problem Based Learning (PBL) learning model in Mathematics subjects could improve the critical thinking skills of fourth grade elementary school students. This result is indicated by the increase in students' critical thinking skills by obtaining an average score in the initial conditions, namely 67.79, which experienced an increase in cycle I, namely 73 and cycle II, namely 86. Based on this research, it can be said that the application of the Problem Based Learning (PBL) learning model can improve students' critical thinking skills in Mathematics in class IV elementary school.